Macau: The Ao Man Long corruption and money laundering case - Jorge Godinho (Freedom from Fear, 2009)
This article summarizes the main issues underlying the case of Ao Man Long, the highest profile corruption case ever occurred in the Macau Special Administrative Region (SAR) of the People’s Republic of China, which attracted international attention. Ao Man Long was the first Secretary for Public Works in the Government of the Macau SAR, a post equivalent to minister to which he was appointed on 20 December 1999, at age 43, and then reappointed in 2004 for a second term. Ao graduated in mechanical engineering from the University of Taiwan, obtained an MBA at the University of Macau, and had served as a Macau civil servant since 1987.